Road Quality and Mean Speed Score - Moszoro, Marian (IMF Working Papers; Working Paper, 2022)
We introduce a novel measure of cross-country road quality based on the travel mean speed between large cities from Google Maps. This measure is useful to assess road infrastructure and access gaps. Our Mean Speed (MS) score is easier to estimate and update than traditional gauges of road network quality which rely on official reports, surveys (i.e., World Economic Forum's Quality of Roads Perception survey), or satellite imaging (i.e., World Bank's Rural Access Index). In a sample of over 160 countries, we find that MS scores range between 38 km/h (23.6 mph) and 107 km/h (66.5 mph). We show that the MS score is a strong proxy for road quality and access.